RETRACTED: Retraction Note: Stopping peculiarities of the iterative algorithm for identifying scenes in at video stream - Alexandrov Islam; Titova Anastasia; Nogmov Muhamed; Karpov Nikita (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001